2015
DOI: 10.5603/ep.2015.0012
|View full text |Cite
|
Sign up to set email alerts
|

Nieradykalne (oszczędzające) operacje guzów nadnerczy

Abstract: Currently, laparoscopic adrenalectomy is seen as more than just the preferred method, in fact as a routine procedure, always bearing in mind, however, the developed restraints on its usage. The size of the tumour, recurrent disease, and the existing invasive process all remain factors which determine the indications for operation. The situation is similar in cases of qualifying for sparing (non-radical) operations on adrenal glands. The basic challenge in terms of qualification, choice of technique and the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Sporadic pheochromocytomas can also be bilateral in approximately 25% of cases, but manifest asynchronously, which also favours sparing surgery [4,9]. Other indications include unilateral adenoma in Conn's or Cushing's syndrome, as well as situations involving bilateral adrenal lesions manifesting synchronously or asynchronously [10]. In our case, a single, usually small adenoma responsible for overproduction of aldosterone is the optimal indication for sparing surgery.…”
Section: Discussionmentioning
confidence: 66%
“…Sporadic pheochromocytomas can also be bilateral in approximately 25% of cases, but manifest asynchronously, which also favours sparing surgery [4,9]. Other indications include unilateral adenoma in Conn's or Cushing's syndrome, as well as situations involving bilateral adrenal lesions manifesting synchronously or asynchronously [10]. In our case, a single, usually small adenoma responsible for overproduction of aldosterone is the optimal indication for sparing surgery.…”
Section: Discussionmentioning
confidence: 66%
“…Another important aspect is the residual adrenal volume. It has been suggested that at least 15% to 30% of adrenal tissue is necessary for normal gland function ( 32 - 34 ), although some report steroid-independence with less than 15% tissue ( 35 ). Nevertheless, there is an unanimous agreement that if the proposed minimal remnant tissue cannot be achieved, LTA should be performed ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…When talking about the remnant volume, the resection margin should also be taken into account. The proposed 3-5 mm margin is considered enough for an adequate outcome ( 34 ). The final aspect is preservation of the adrenal vein.…”
Section: Discussionmentioning
confidence: 99%
“…For this procedure, the tumour is excised with a 3-5 mm margin of healthy tissue while preserving one quarter to one third of the adrenal cortex, which ensures proper hormonal function. However, the oncological safety of such procedures requires preoperative information concerning low risk of malignant processes [13]. At present, adrenal-sparing surgeries (one-sided or bilateral) are performed in patients at high risk of developing a second tumour in the opposite adrenal gland with a predicted mild course of the disease.…”
Section: Methodsmentioning
confidence: 99%